CURRENT APPROACHES IN THE DIAGNOSIS AND MANAGEMENT OF PULPITIS (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Pulpitis remains one of the most common and clinically significant inflammatory conditions in dentistry, primarily resulting from microbial invasion and subsequent activation of host immune responses. Although the etiology is well understood—most often linked to dental caries, trauma, or restorative procedures—the complexity of pulp tissue reactions continues to challenge clinicians. When bacterial metabolites penetrate dentinal tubules, the pulp responds with localized inflammation that can rapidly progress if left untreated. The confined nature of the pulp chamber, combined with limited vascular supply, means that even minor inflammatory changes can lead to severe pain and structural compromise.